Exploring the effectiveness of extensive reading on incidental vocabulary acquisition by EFL learners: an experimental case study in a Libyan University - Alahirsh, Hamed (2014)
Considerable worldwide research has investigated incidental vocabulary learning from L2 reading, yet so far nothing has been published about the actual learning that comes from reading various texts. This study investigated incidental lexical growth and retention by Libyan university EFL majors who were involved in a two-month ER programme. Their vocabulary gain was measured 1 week after the participants completed the Extensive Reading (ER) programme, 2 weeks later and 9 months later. The value of this study is that it used an innovative approach, which was developed from a research design by Horst (2005). This included the electronic scanning of books and lexical frequency profiling, helping the researcher to create individualised corpus profiles from the entire set of different texts the participants read. This data was then used to select target words for each participant. The methodology was an experimental case study, which entailed an experimental and control group design. The participants were EFL learners who studied English as their subject of specialisation in one of eight Libyan state universities. An original number of 80 participants were randomly selected from the entire population in the English Language Department and assigned equally between the experimental and control groups. However, due to the fact that this study was carried out in very anomalous circumstances (during the Libyan uprising, which started on 15/02/2011), the number of participants who successfully completed the ER programme was affected (18 participants in each group). The study showed that by using a corpus analysis strategy, it was feasible to measure learners’ individualised pre-post treatment acquisition of the vocabulary they encountered in a large number of ER graded texts. The findings of the study demonstrate that ER significantly improved the Libyan EFL learners’ incidental vocabulary acquisition. By the end of the study, it was found that about the third of the target words had been acquired by the participants at both receptive and productive levels of knowledge. The findings further indicate that word repetition was an important factor for an incidental pick up of vocabulary from the ER. In relation to long-term retention rate of learning, the findings suggest that incidental word knowledge, acquired through ER, significantly declines over time.